Entrepreneurship and innovation in automobile insurance : Samuel P. Black, Jr. and the rise of Erie Insurance, 1923-1961 /: Samuel P. Black, Jr. and the rise of Erie Insurance, 1923-1961. ([2019?]) - Black, Samuel P (Samuel Patton), 1902-; Rossi, John Paul
No abstract available